Pamida y metformina como hipoglicemiantes orales y el extracto acuoso de las hojas de Smallanthus sonchifolius (Poepp) Rob. "Yacón" por hiperglicemia experimental en Rattus norvegicus var. albina - Castro L., Américo J. (2006)
It was carried out the comparative evaluation of three synthetic drugs used as oral hypoglycemiants, against the aqueous obtained by infusion of leaves from Smallantus sonchifolius (Poepp) Rob. Yacon , using a experimental biomodel by hypoglycemia in normoglycemic rats of species Rattus norvegicus Var. Albine. The object of the research was to observe the 10 % aqueous extract effect of Smallantus sonchifolius (Poepp) Rob. Yacon in the decay of glycemia against glibenclamide, c1orprofamide and metformine drugs that have great usage in the treatment of type 2 diabetes mellitus (DM2). The vegetal material was collected in the Huancabamba district, province of Oxapampa in Cerro de Pasco department. The pharmaeological assay was taken with 36 female albine rats of Holtzman strain , with a average weight of 240g that were fed by a controlled foad and water ad libitum until the moment of experiment. It was determined the glucose tolerance curve and the administration of drugs was made by intragastric via. The obtained results show a significant decay of glycemia with the used aqueous extract. With the extract and the drugs used in the experimental biomodel, it was concluded that the Yacon leaves produce an effect of significant decay of glycemia .